Sanda. 1 - Itagaki, Paru, 1993- (Titan Comics, 2025)
Join Sanda and Shiori on an unforgettable journey to restore the magic of Christmas, uncovering secrets, friendship, and adventure in a future Japan. In a near-future Japan, Christmas has faded into myth, and the birth rate has dropped so dramatically that children are now the most precious commodity. Society has artificially extended adolescence to preserve their youth, and traditional holidays, like Christmas, are a mere legend of the past. Volume 1 of Sanda introduces Sanda Kazushige, a middle-school student who unexpectedly becomes entangled in a strange and dangerous mystery. When his classmate, Fuyumura Shiori, accuses him of carrying a curse that could help find her missing friend, Ono Ichie, Sanda's life takes a dramatic turn. Together, they embark on an incredible adventure to unravel the truth behind Ichie's disappearance and uncover the hidden magic of Christmas itself. As they delve deeper into the mystery, the duo faces external threats and internal challenges--questions about loyalty, courage, and the power of belief. Along the way, they confront the true meaning of friendship, trust, and the possibility of magic in a world that has all but forgotten it. With a mix of supernatural elements, heartfelt moments, and a nostalgic quest to restore childhood wonder, Sanda Volume 1 kicks off a sixteen-volume saga blending mystery, adventure, and emotional depth. The series is also being adapted into an anime, so fans can dive further into the world of Sanda.